An Assessment of Glacier Inventories for the Third Pole Region - He, Xia; Zhou, Shiqiao (Frontiers in Earth Science, 2022)
A glacier inventory contains data that are important for understanding the hydrology, water resources, and impacts of climate change in glaciated regions. Ten glacier inventories have been created for the Third Pole Region (TPR) or high-mountain Asia, but they vary largely in spatial coverage area and data quality. Therefore, it is necessary to assess the data quality to help potential users choose the right glacier inventories for their research. Using the analytical hierarchy process, this study selects eight assessment factors and quantifies the quality of eight glacier inventories of the TPR. The eight glacier inventories that we assessed are the Randolph Glacier Inventory (RGI), the Glacier Area Mapping for Discharge in Asian Mountains (GGI18), the Second Chinese Glacier Inventory (CGI-2), the Glacier Inventory of the Hindu Kush–Himalayan Region (HKHGI), the Glacier Inventory for the Western Himalayas (WHGI), the Glacier Inventory for the Karakoram and Pamir Region (KPGI), the Second Glacier Inventory of Pakistan (PGI-2) and the Glacier Inventory for the Southeastern Tibetan Plateau (SETPGI). The assessment results indicate that the overall quality of the small-scale glacier inventories of WHGI, KPGI, PGI-2, and SETPGI is higher than that of the large-scale inventories of RGI, GGI18, CGI-2, and HKHGI. For the large-scale inventories, the quality-ranking order from high to low is CGI-2, GGI18, RGI, and HKHGI. However, the comprehensive quality of CGI-2 and GGI18 is comparable over the area covered by CGI-2. The comprehensive quality of CGI-2, GGI18, and RGI exhibits clear spatial differences. Overall, the data quality is higher for the inner TPR than for the surrounding areas. By merging the products of the eight glacier inventories, a new glacier inventory product of the best comprehensive quality was derived for the entire TPR. This new product resembles the spatial distribution of the best-quality glacier inventories of the regions where the different products overlap. In terms of specific regions, the CGI-2 and GGI18 are the best products for most parts of the TPR in China, except for an area of southeastern Tibet where the highest-quality data are from the SETPGI. The other main distributions of the best products are the WHGI for the western Himalayas, the GGI18 and HKHGI for the Hindu Kush and the middle and eastern Himalayas, the PGI-2 for Pakistan, the KPGI for the Karakorum–Pamir area, and the GGI18 and CGI-2 for the Tianshan Mountains. The new data product greatly promotes the quality of a single glacier inventory for the entire TPR. This database will meet the needs of a variety of potential researchers, including those who prefer to get information for a particular parameter from a single glacier inventory (http://data.tpdc.ac.cn/en/data).